From review to reform: designing an elective module through an integrated review on fashion sustainability - Khar, Sonika Soni (Frontiers in Sustainability, 2025)
BackgroundSustainability in fashion design education is crucial to address environmental and social challenges posed by the fashion industry. At present, fashion design education still offers mainstream fashion design courses that scarcely incorporate sustainability within their curricula. A well-defined educational framework that emphasizes environmental, economic, and social dimensions of sustainability in ways that are both theoretical and practical is required.MethodsThis study is an integrative review of 81 papers from peer reviewed journals on fashion and textile education, sustainability, consumer behavior and technology from 2014 to 2024. A systematic approach of indexing and categorizing research articles was formulated. By synthesizing research, this study identified fundamental framework on three major key aspects of sustainability viz., environmental, economic and social. A systematic approach of indexing and categorizing research articles was formulated.ResultsA multifaceted evaluation of these three aspects proposes a new theoretical framework which can be implemented in two stages as an elective of 2 weeks duration to the undergraduate students. To enhance the effectiveness of these electives, Bloom’s Taxonomy was incorporated as a tool in this framework to ensure that learning outcomes progress from basic knowledge acquisition to higher-order skills such as analysis, synthesis, and evaluation.ConclusionThe proposed theoretical and practical modules offer a comprehensive framework that fosters both conceptual awareness and hands-on application, aligning with experiential learning strategies and Bloom’s hierarchical cognitive development. This framework can serve as a model for curriculum development, ensuring that sustainability remains a core pillar of fashion education.